BAPNE as a Neurodidactic Strategy for the Development of Executive Functions in Physical Education - León López, Luiggi Wladimir (Revista Internacional de Pedagogía de la Actividad Física y Deporte, 2026)
This research aims to strengthen the training of future Physical Education teachers through a solid theoretical foundation, integrating an active, inclusive methodology aligned with the educational demands of the 21st century. The BAPNE method, focused on body percussion, stimulates brain  activity  through  multiple  stimuli,  activating  both  hemispheres  and promoting anátomo-functional, biopsychosocial, and psychomotor integration.Objective: To innovate the teaching of Physical Education within the framework of the Ecuadorian curriculum by incorporating the BAPNE method, aimed at enhancing kinesthetic intelligence and executive functions in children and adolescents in today’s society.Methodology: From the total population, a sample of 20% (100 students) from a basic education institution was selected, including sublevels from Early Childhood to Upper Basic. These students participated in 8 pedagogical Physical Education sessions implemented using the BAPNE method. Mixed instruments were used, including the adapted BRIEF-2 test, the teacher’s reflective journal, focus group interviews, and a motor performance test based on the Psychomotor Development Scale (EDP).Results: The development phases of the project include an initial diagnosis, analysis of results from a global perspective based on the BAPNE method, scientific production, teacher training, and the creation of a methodological guide. Conclusions: The design of a globalized didactic program based on this methodology enables the structuring of educational planning according to the development of multiple intelligences, with an emphasis on kinesthetic intelligence. The sequential organization of the program ensures that it can be easily adapted to different educational levels